Assessment of cyclin D1 activity in tumors and tumor budding and its prognostic significance in tumor budding in colorectal carcinomas - Coban, Ganime; Arici, Dilek S.; Tekden, Busra C.; Yildiz, Pelin; Kiran, Tugce; Toluk, Özlem; Turk, Haci M.; Şahin, Nurhan (Indian journal of pathology & microbiology, 2024)
ABSTRACT Background: The most important prognostic parameter is staging in colorectal cancers, and tumor budding (TB) is among the independent prognostic parameters that are increasing in significance. Cyclin D1 expression has been associated with poor prognosis as a marker of various tumors. Aims and Objectives: In this study, the aim was to determine the activity of cyclin D1 in colon adenocarcinomas, tumors, and tumor buds and to compare the results with prognostic parameters. Materials and Methods: This study included 167 patients who were operated on for colorectal tumors. In subjects, tumor budding was evaluated on hematoxylin and eosin-stained slides, and cyclin D1 was applied immunohistochemically. The cyclin D1 intensity of staining was studied in both tumors and TB and its correlation with prognostic parameters in TB was examined. Results: Lymph node (LN) metastasis was present in 93 (55.7%) of the cases, and distant metastasis in 35 (21%) cases. Tumor budding was present in 152 (91%) of the cases, and high-grade TB was detected in 55 (36.2%). The incidence of TB was higher in patients with LN metastasis (P = 0.02) and in patients with Stages 3 and 4 (P = 0.07). The intensity of cyclin D1 in intermediate and high-grade TB staining was higher. Cyclin D1 staining was more intense in patients with LN metastases and distant metastases as we determined, but it was not statistically significant. Conclusion: Thus, based on our study findings, the increased expression of cyclin D1, which is more concentrated in TB than tumors, may indicate a poor prognosis. In contrast, we found no statistically significant correlation between cyclin D activity and prognostic parameters in TB.